«ЭТО ПОНЯТИЕ РАСТЯЖИМОЕ…»: ЦЕНТР ГОРОДА В УСТНЫХ РАССКАЗАХ ПЕРМЯКОВ (Filološke studije, 2019)
The paper deals with contemporary ideas of Perm inhabitants concerning the centre of the city, the localization of which reflects the general peculiarities of Perm’s spatial self-identification. The material for the research is presented by oral accounts by Perm inhabitants. The latter have been collected within the limits of the Perm state University research project “The verbal history of Perm”. The ideas of Perm inhabitants concerning the centre of the city have revealed the fact of gradual getting accustomed to its drift to the south-west (it is the direction that determines the main vector of the city’s development), and its division into various functional zones: historical centre (old Perm), commercial centre (Komsomolskiy Prospect and Central Department store), administrative-transport and recreative centre (esplanade). At the same time the general vagueness, resulting from the influence of geographical landscape and historical and cultural peculiarities, remains the dominating motive in the image of the Perm centre. The plans for the reconstruction of the Perm centre are supposed to take into consideration the peculiarities of the spatial adaptation peculiar of the majority of the inhabitants. The reduction of the vagueness degree seems to be connected with the constructive attitude to the functional division of the centre that has been made up in the public opinion.